1992
DOI: 10.1021/jm00096a013
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor imidazotetrazines. 25. Crystal structure of 8-carbamoyl-3-methylimidazo[5,1-d]-1,2,3,5-tetrazin-4(3H)-one (temozolomide) and structural comparisons with the related drugs mitozolomide and DTIC

Abstract: The antitumor imidazotetrazinone, temozolomide (5), C6H6N6O2, forms crystals with unit cell dimensions a = 17.332 (3), b = 7.351 (2), c = 13.247 (1), beta = 109.56 (1) degree and space group P21/c. A doubly hydrogen-bonded dimer constitutes the asymmetric unit. One carboxamide group forms an additional intermolecular NH...O hydrogen bond; in both molecules the carboxamide group is coplanar with the heterocycle and its NH2 group interacts with the imidazole nitrogen atom N(7). Molecular orbital calculations sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 4 publications
1
23
1
1
Order By: Relevance
“…Ten polymorphs of TMZ are covered in the patent literature [31,32], of which four have had X-ray structures solved [33,34]. TMZ can easily form a dimer via intermolecular hydrogen bonds between the carboxamide groups (Figure 7).…”
Section: Temozolomide Co-crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten polymorphs of TMZ are covered in the patent literature [31,32], of which four have had X-ray structures solved [33,34]. TMZ can easily form a dimer via intermolecular hydrogen bonds between the carboxamide groups (Figure 7).…”
Section: Temozolomide Co-crystalsmentioning
confidence: 99%
“…TMZ can easily form a dimer via intermolecular hydrogen bonds between the carboxamide groups (Figure 7). It has also been proposed that the energetic preference for the observed conformer can be attributed to an intramolecular hydrogen bonding interaction between amide NH and imidazole N 7, although this shows significant (74°) deviation from linearity [27,33]. …”
Section: Temozolomide Co-crystalsmentioning
confidence: 99%
“…At physiological pH, temozolomide transforms into its active metabolite, 5-(3-methyltriazene-1-yl)imidazole-4 carboxamide (MTIC), which is mostly excreted by the kidneys, and rapidly disappears from the blood [5, 6]. Temozolomide is less toxic and more predictable than mitozolomide with comparable antitumor activity [7, 8]. An alkylating agent stable under acid conditions, temozolomide survives the highly acidic stomach environment, so it can be administered orally in capsules; when administered orally, absorption is rapid and essentially complete, and peak plasma concentration is achieved within 0.5 h; bioavailability after oral administration is similar and approximately 100% [9].…”
Section: Introductionmentioning
confidence: 99%
“…While the amide at C8 had been suggested in the past to be essential for activity, 2,16 conflicting reports have since indicated that alternate functionality may be tolerated at this position. 17−19 Indeed, our own analysis led us to believe that strategic substitutions at C8 could be used to tune the hydrolytic stability of imidazotetrazines, and that in doing so, a suite of compounds with a range of half-lives could be constructed.…”
mentioning
confidence: 99%